Approaches for evaluating the NRC Resident Research Associateship Program at NIST - Sislin, John, 1965- (National Academies Press, 2007)
The NRC Resident Research Associateship Program at NIST provides two-year temporary appointments for outstanding scientists and engineers. This report describes program applicants and awardees and offers suggestions for an in-depth assessment of career outcomes. Preliminary investigation indicates that outreach efforts produce more qualified applicants than NIST has slots to fill, the pool of applicants is increasingly diverse, and many Research Associates go on to permanent positions at NIST. The agency should conduct a more thorough evaluation of the program, including an assessment of outreach to potential applicants, individuals who decline an award, the program's impact on the careers of awardees, and the benefits of the program to NIST and the broader scientific and engineering community.